Mindfulness-based interventions and student wellbeing: can digital group meetings enhance app-based training? - Zinke, Nikolai; Ritz, Anne; Bunzeck, Nico (Frontiers in Education, 2025)
IntroductionUniversity students are experiencing more and more stress, which can negatively impact their mental health. Therefore, new ways are needed to address this issue. To this end, we examined the effectiveness of an app-delivered mindfulness-based stress training and a possible interaction with additional group meetings within a university setting.MethodsA randomized mixed experimental design was used to assess an 8-weeks Mindfulness-Based Intervention (MBI) delivered via podcasts and supplemented by group meetings, either in video calls (VC) or a virtual reality (VR) environment. The intervention aimed to improve mental health, focusing on risk factors stress and loneliness as well as protective factors such as self-compassion and self-efficacy.ResultsOur results indicated partial overall effectiveness of the MBI, with significant reductions in stress experience and loneliness and increases in self-compassion, yet all at the facet level. Exploratory analyses revealed that group meetings enhanced mindfulness, which in turn contributed to stress reduction, but the relationships of VR immersion and stress reduction yielded mixed results.DiscussionOur findings give novel insights into how the specific positive effects of the MBI might interact with digital group meetings, which could pave the way for further research with optimized intervention settings.